The obligation of guarantee safety in maritime passenger transport - Aichour, Abdessalam; Badreddine, Younes (Journal of Human Sciences, 2021)
The solution adopted  by the Brussels convention in 1961- solution which will be taken up in the new French act 1966- as by Algerian maritime law, made the obligation of the maritime carrier to ensure safety only an obligation of means, based on a double observation. The first is the freedom of the passenger on board a ship, the liability of the carrier can only be based on the fault. The second observation is that it is impossible for passenger to prove the specific circumstances that led to injury or death, in the case of a group accident. Liability of the carrier based on presumptions of fault. The fulfillment of this obligation is linked to the availability of a contract which obliges the traveler to pay the cost of passage, and of a bodily accident produced during the period of transport